2018
DOI: 10.3390/ma11050793
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Damage Effects on MgO Added Concrete with Slag Cement Exposed to Calcium Chloride Deicing Salt

Abstract: Concrete systems exposed to deicers are damaged in physical and chemical ways. In mitigating the damage from CaCl2 deicers, the usage of ground slag cement and MgO are investigated. Ordinary Portland cement (OPC) and slag cement are used in different proportions as the binding material, and MgO in doses of 0%, 5%, 7%, and 10% are added to the systems. After 28 days of water-curing, the specimens are immersed in 30% CaCl2 solution by mass for 180 days. Compressive strength test, carbonation test, chloride penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…e procedure to sections preparation is according to the literature [35]. After exposed to 140 days of drying-wetting cycles in 5% Na 2 SO 4 solution, the cubic specimen was cut into 5 sections, each of which is 28 mm (2 mm reduction due to cutting wear).…”
Section: Section Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…e procedure to sections preparation is according to the literature [35]. After exposed to 140 days of drying-wetting cycles in 5% Na 2 SO 4 solution, the cubic specimen was cut into 5 sections, each of which is 28 mm (2 mm reduction due to cutting wear).…”
Section: Section Preparationmentioning
confidence: 99%
“…is is mainly because the polypropylene fibers restrain the pores diameter to enlarge [25], further making the whole structure of the concrete more complete [9,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: E Pores Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was verified that the use of GGBFS can improve the microstructures of concrete by adding a C-S-H phase, and it is effective in reducing the conductivity of chloride due to its provision of an increased alumina content [19]. Jang et al [20] conducted a 180-day immersion test with a 30% CaCl 2 solution and reported that the system with GGBFS and MgO endured damage far more effectively. Cheng et al [21] claimed that the partial substitution of cement with GGBFS had a significant effect on the total flexural stiffness, corrosion rate, and permeability of a fabricated concrete beam.…”
Section: Introductionmentioning
confidence: 98%
“…The MgO–SiO 2 –H 2 O system was developed as a novel cementitious material [1,2,3,4,5]. Numerous applications have been realized, including usage in thermal insulation material [6], waste sealing material [7], refractory material [8], and soil stabilization [9].…”
Section: Introductionmentioning
confidence: 99%